2023
DOI: 10.1038/s41598-023-40651-2
|View full text |Cite
|
Sign up to set email alerts
|

Generation of multi-scrolls in corona virus disease 2019 (COVID-19) chaotic system and its impact on the zero-covid policy

Muhammad Marwan,
Maoan Han,
Rizwan Khan

Abstract: In this paper, we discussed the impossibility of achieving zero-covid cases per day for all time with the help of fuzzy theory, while how a single case can trigger chaotic situation in the nearby city is elaborated using multi-scrolls. To accomplish this goal, we consider the number of new cases per day; $$x_{1}$$ x 1 to be the preferred state variable by restricting its value to the interval (0, 1). One can need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Moreover, the research on covid-19 is not restricted to biology, but a lot of work can be found in other fields as well, such as, Machine learning [ 6 , 7 ], dynamical systems [ 8 , 9 ]. The covid-19 model [ 10 , 11 ] that we have considered is where , and shows the daily numbers of new cases, daily additional severe cases and new death cases reported per day due to covid, respectively. Mathematically, system ( 2 ) exhibits chaotic behaviour for initial conditions =(184, 30, 8) and parameter values given in Table 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the research on covid-19 is not restricted to biology, but a lot of work can be found in other fields as well, such as, Machine learning [ 6 , 7 ], dynamical systems [ 8 , 9 ]. The covid-19 model [ 10 , 11 ] that we have considered is where , and shows the daily numbers of new cases, daily additional severe cases and new death cases reported per day due to covid, respectively. Mathematically, system ( 2 ) exhibits chaotic behaviour for initial conditions =(184, 30, 8) and parameter values given in Table 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the research on covid-19 is not restricted to biology, but a lot of work can be found in other fields as well, such as, Machine learning [6,7], dynamical systems [8,9]. The covid-19 model [10,11] that we have considered is…”
Section: Introductionmentioning
confidence: 99%